2010
DOI: 10.1016/j.jfa.2009.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Direct limits, multiresolution analyses, and wavelets

Abstract: A multiresolution analysis for a Hilbert space realizes the Hilbert space as the direct limit of an increasing sequence of closed subspaces. In a previous paper, we showed how, conversely, direct limits could be used to construct Hilbert spaces which have multiresolution analyses with desired properties. In this paper, we use direct limits, and in particular the universal property which characterizes them, to construct wavelet bases in a variety of concrete Hilbert spaces of functions. Our results apply to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 17 publications
(58 reference statements)
0
35
0
Order By: Relevance
“…We can construct measures on E ∞ by viewing it as an inverse limit lim ← − (E n , r n ), where r n : E n+1 → E n takes ν = ν 1 ν 2 · · · ν n ν n+1 to ν 1 ν 2 · · · ν n . Then any family of measures δ n on E n such that δ n+1 (Z(ν) ∩ E n+1 ) = δ n (Z(ν)) for |ν| = n gives a measure δ on E ∞ such that δ(Z(ν)) = δ n (Z(ν)) for |ν| = n (see, for example, Lemma 6.1 of [1]). We can construct such a sequence by taking δ 0 = ε, inductively choosing weights w e such that r(e)=v w e = ε v , recursively choosing {w νe ∈ [0, ∞) : νe ∈ E n+1 } such that r(e)=s(ν) w νe = w ν , and setting δ n+1 (νe) = w νe .…”
Section: The Shift On the Path Space Of A Graphmentioning
confidence: 99%
“…We can construct measures on E ∞ by viewing it as an inverse limit lim ← − (E n , r n ), where r n : E n+1 → E n takes ν = ν 1 ν 2 · · · ν n ν n+1 to ν 1 ν 2 · · · ν n . Then any family of measures δ n on E n such that δ n+1 (Z(ν) ∩ E n+1 ) = δ n (Z(ν)) for |ν| = n gives a measure δ on E ∞ such that δ(Z(ν)) = δ n (Z(ν)) for |ν| = n (see, for example, Lemma 6.1 of [1]). We can construct such a sequence by taking δ 0 = ε, inductively choosing weights w e such that r(e)=v w e = ε v , recursively choosing {w νe ∈ [0, ∞) : νe ∈ E n+1 } such that r(e)=s(ν) w νe = w ν , and setting δ n+1 (νe) = w νe .…”
Section: The Shift On the Path Space Of A Graphmentioning
confidence: 99%
“…However, it does not seem to be so easy to find natural Hilbert space representations of O(M L ) in which the KMS log | det A| state is a vector state. [4], or more precisely, one of the more general sort studied in [2].…”
Section: Kms States Formentioning
confidence: 99%
“…As for the system in [23], the circular symmetry at β = log N which disappears for β > log N is not apparently realised by an action of T on T (N ⋊ N N). In [23], though, this circular symmetry persists for β ∈ [1,2], as a result of the more complicated convergence issues for the series representations of the normalising factors.…”
Section: Parametrisation Of Kmsmentioning
confidence: 99%
“…Dutkay and Jorgensen [16] pioneered the study of wavelets in function spaces on fractals, with later work by D'Andrea et al [14]. Larsen, Raeburn and coworkers then showed that these and other interesting examples can be constructed via direct limits [19,4,5]. Dutkay et al [9,17] constructed MRAs and super-wavelets in Hilbert spaces formed by direct sums of L 2 (R d ) to orthonormalize examples such as the Cohen wavelet.…”
Section: Introductionmentioning
confidence: 99%